A new species of the ghost shrimp genus Neocallichirus Sakai, 1988 from Iran, and new record of N. manningi Kazmi & Kazmi, 1992 (Decapoda: Axiidea: Callianassidae) - Sepahvand, Vahid; Komai, Tomoyuki; Momtazi, Farzaneh; Shahabi, Saeed (Zootaxa, 2018)
Two species of the callianassid ghost shrimp genus Neocallichirus Sakai, 1988 are newly recorded from Iran. Neocallichirus darvishi n. sp. appears close to N. jousseaumei (Nobili, 1904), but combined morphological and genetic analyses provide evidence for recognition of the new taxon. Neocallichirus manningi Kazmi & Kazmi, 1992, originally described from Pakistan, is reported for the first time since its original description. A supplemental description and figures are given for N. manningi.